Pedagogical Conditions of Ethno-Pedagogic Culture Development In Future Teachers - Inomjon Ugli, Nematov Mashxurbek (Innovative Technologica: Methodical Research Journal, 2024)
This article analyzes the pedagogical conditions for the development of ethnopedagogical culture in future teachers. Ethno-pedagogical culture is a deep understanding of national and traditional values, their effective application in the educational process, and the ability to convey them to the younger generation. The article describes the essence of ethnopedagogical culture, its components, as well as the main pedagogical conditions necessary for its development. An analysis of effectiveness is given as an example of innovative approaches and methods used in practice in the educational system.